Passive design strategies of colonial mosques in Malaysia - Sanusi, Aliyah Nur Zafirah; Azmin, Aida Kesuma; Abdullah, Fadzidah; Kassim, Mohd Hisyammudin (Springer, 2019)
Mosque architecture in Malaysia has been classified into three different styles; Vernacular, Colonial and Modern. This paper focused on evaluating the passive design strategies adopted in Colonial style mosques. In general, Colonial building styles were built from the 17th to the 20th centuries. This style was brought in by the Europeans, depicting the architecture style of the West. Therefore, this study is intended to evaluate the strategies of climatic adaptation of Colonial Architecture style Mosques in Malaysia climate. The first objective of this study is to identify the passive design elements found in three (3) case studies of Royal Colonial Mosques in Malaysia, while the second objective is to evaluate the significance and effectiveness of the passive design strategies adopted by Colonial style mosques in Malaysia. The study methodology comprises of three stages. Firstly, the observation and literature review on the Colonial Mosques, secondly, the simulation of the indoor environment of three (3) Colonial Mosques case studies, and thirdly, the analysis of results obtained from observation and simulation. It was concluded that colonial design elements found in the three (3) Colonial Mosques are responsive to the Malaysian climate and are significant and effective. All three Royal Colonial mosques adopted five passive design strategies. Among the five, the most significant and effective passive design strategies is the Verandah, which gives full protection of the openings from the solar radiation. In addition to that, the introduction of the dome into mosque design contributes to the improvement of the indoor environment. The dome provides a large roof space, which protects the indoor space from solar radiation. Colonial architecture style Mosques was influenced by Western architecture, which are usually designed for temperate countries. However, the colonial architecture was adapted to the Malaysian climate for Colonial Mosques design and provide a comfortable indoor environment to the Mosques.